Characterizing AA6351/Tib2 Composite Drilling on Abrasive Water Jet Machining (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
Aluminum is a material that is malleable, soft, and resistant to corrosion. Additionally, it has a high electrical conductivity. It finds widespread application in the production of conductor cables and foil, but it must be alloyed with other elements in order to achieve the greater strengths required for usage in other applications. Aluminum, which has a strength-to-weight ratio that is superior to that of steel, is one of the lightest engineering metals you can find. The purpose of this work is to investigate the microstructural and drilling characterisation of AA6351/TiB2 composites that were produced using the stir casting method. In order to determine the process parameters, the weight percentage of TiB2 was varied between 5 and 10. In order to determine the hardness and optical microstructure of the composites that were fabricated, as well as the effects of machining parameters such as surface roughness and circularity of the composites, the experiments were carried out by using Al-6351 as the workpiece. The drilling process was carried out by an abrasive water jet machine. The value of the result demonstrates that the hardness value has been steadily increasing.